(untitled) (Universa Medicina, 2016)
Diabetes mellitus (DM) is an important global cause of mortality, morbidity, and health-system costs,(1,2) with significant increases in its prevalence and number of cases in the last 30 years. It constitutes one of the four non communicable diseases (NCDs) targeted for action by world leaders.According to WHO estimates, in 2014 there were 422 million adults with DM aged 18 years or older, with around half in the WHO South-East Asia and Western Pacific Regions.(3) The prevalence of DM and the number of adults with DM in low- and middle-income countries have over the last decade increased at a greater rate than in high-income countries. The global DM prevalence increased by more than 100% in men and by 60% in women, resulting in a predominance of males with DM in 2014 as compared with a higher DM female prevalence in 1980.